Networks in marketing - Jacobucci, Dawn (Housand Oaks, California: Sage Publications, 1996)
Contents: Part 1. Marketing is realtional, Part 2. The network paradigm allows the study of relational phenomena, Part 3. Theorical concepts of networks for marketers, Part 4. Dynamics networks, Part 6. Final issues.
Referencias p. 410-436
Keywords: Marketing; Relaciones Públicas